Employee Trust and Workplace Performance - Sarah Brown; Daniel Gray; Jolian McHardy; Karl Taylor (Institute for the Study of Labor (IZA), 2014)
We explore the relationship between employee trust of managers and workplace performance. We present a theoretical framework which serves to establish a link between employee trust and firm performance as well as to identify possible mechanisms through which the relationship may operate. We then analyse matched workplace and employee data in order to ascertain whether the average level of employee trust within the workplace influences workplace performance. We exploit the 2004 and 2011 Work Place and Employee Relations Surveys (WERS) to analyse the role of employee trust in influencing workplace performance in both pre and post recessionary periods. Our empirical findings support a positive relationship between three measures of workplace performance (financial performance, labour productivity and product or service quality) and employee trust at both points in time. We then exploit employee level data from the WERS to ascertain the determinants of employee trust as well as how trust is influenced by measures taken by employers to deal with the recent recession. Our findings suggest that restricting paid overtime and access to training potentially erode employee trust. In addition, we find that job or work reorganisation experienced at either the employee or organisation level are associated with lower employee trust.
Keywords: J20; J50; 330; employee trust; financial performance; labour productivity; product quality